Indonesian Telemedicine Regulation to Provide Legal Protection for Patient - Tiara Tiolince (Journal of Sustainable Development and Regulatory Issues, 2023)
The objective of this study is to identify the underlying factors contributing to the absence of legal safeguards for patients in Indonesia with respect to Telemedicine arrangements. Additionally, this research endeavors to develop an optimal framework for Telemedicine arrangements in Indonesia that would ensure legal protection for patients. The present study constitutes a normative legal research. The author posits that in order to provide legal protection for optimal patients, it is necessary to regulate telemedicine services. This can be achieved by implementing a system that guarantees measurable and certified competence in telemedicine services. The proposed framework includes several key components. Firstly, it emphasizes the importance of clearly defining domain areas. Secondly, it underscores the obligation to record telemedicine service practices and protect such recordings. Thirdly, it outlines regulations pertaining to informed consent. Fourthly, it incorporates arrangements for dispute resolution in the context of health services provided to patients via telemedicine.